Postharvest Quality Evaluation of Feijoa Fruits (Acca sellowiana (Berg) Burret) - Silveira, Ana Cecilia; Oyarzún, Dennise; Rivas, Mercedes; Záccari, Fernanda (Agrociencia Uruguay, 2016)
The feijoa (Acca sellowiana (Berg) Burret- Rutaceae) is commercially exploited in several countries, which has awakened the interest of the national breeding programs in order to identify materials suitable for commercial exploitation. In this work fruit of 14 different genetic materials were evaluated during storage for 8 and 15 days at 5 ± 1 °C, in order to identify better postharvest behavior. Flesh firmness was evaluated and it was higher in the materials 171 and 191, and declined 10-38 % after 8 days and 30-63 % after 15 days at 5 ± 1 °C . Also total solid soluble (TSS) contents remained constant over the conservation of material being greater in 84 and 246. Ascorbic acid (AA) decreased during the storage period, the highest content corresponded to the material 191 with 48.92 ± 1.74 mg AA/ 100 g fresh weight (FW). Differences among total polyphenols (TP) were determined, with values between 359.04 ± 4.12 and 196.5 ± 8.37 mg gallic acid equivalents /100 g FW at harvest. The highest contents corresponded to materials 171, 191 and 204. Finally the total antioxidant capacity (TAC), also reflected differences between materials, since it depends directly on the previously mentioned compounds. The highest values were registered on materials identified with numbers 44, 60, 171, 191 and 204. Both, TP and TAC, decreased during the storage period. The results obtained evidence differences between the analyzed materials, where the most interesting are those identified with numbers 171, 191 and 204.